Drgająca dyfuzja wiedzy w przedsiębiorstwach sieciowych - Perechuda, Kazimierz (Dynamic Diffusion of the Knowledge in the Net Enterprise, 2005)
In the paper are presented: the essence of the net enterprise,- the correlations between tacit and open knowledge,- the absorption of the knowledge in the net enterprise,- the role of the friendly net in the creation and diffusion of the knowledge
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 343-349